Pengaruh Pendidikan Kesehatan Terhadap Tingkat Kemandirian Keluarga Merawat Penderita Tuberkulosis Program DOTS - Isymiarni Syarif; Baso Witman Adiaksa (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Pulmonary tuberculosis is an infectious disease that is still a public health problem in the world. The study aims to determine the level of independence of tuberculosis patients and families before and after the provision of health education. The research design used in this study is a pre-experimental method with one group pretest-postest design. The population of this study was all families who had family members suffering from Pulmonary Tuberculosis and were undergoing treatment ≤ 2 months, the sampling method used was purposive sampling. The results showed the effect of health education on family independence in caring for patients with Pulmonary Tuberculosis DOTS program, with a value of p = 0.005 which means p < α (0.05). It can be concluded that there is an influence of health education on the level of family independence in caring for tuberculosis patients. The results of this study, it is expected that the public health center will socialize the implementation of home care nursing, for tuberculosis patients to always take medication regularly, and future researchers are expected to use different research methods, tests, and variables as well as large samples